Translation Strategies of Figurative Language in the Novel The Fault in Our Stars - Deby Angelia (Institute of Research and Community Outreach - Petra Christian University, 2020)
This research wanted to help the reader to understand about the classification of translation strategies in the novel The Fault in Our Stars. The writer used Larson’s (1998), proposes three strategies to translate figurative language. The writer was interested in analyzing the figurative language because there are many kinds of implicit meaning in figurative language; she felt that it was interesting to be analyzed. Besides, the writer chose a novel because it explains the story more detail than others such as movie. She chose The Fault in Our Stars novel because the story is quite touched and there are a lot of figurative languages on its novel. The writer hope that the translated meaning of figurative language can be the same as the original text. Keywords: Translation, Translation Strategy, Figurative Language, Source Language, Target Language.